Effect of social class at birth on risk and presentation of schizophrenia: case-control study. Issue 7326 (15th December 2001) - Mulvany, Fiona; O'Callaghan, Eadbhard; Takei, Noriyoshi; Byrne, Majella; Fearon, Paul; Larkin, Conall
Abstract: Objectives: To examine if low parental social class increases children's risk of subsequently developing schizophrenia or modifies the presentation. Design: Case-control study with historical controls. Setting: Geographically defined region in south Dublin. Participants: 352 patients with first presentation of schizophrenia matched with the next registered same sex birth from the same birth registration district. Main outcome measures: Social class at birth. Age at presentation to psychiatric services, admission to hospital, and diagnosis of schizophrenia. Results: Risk of schizophrenia was not increased in people from lower social classes. There was a slight excess risk among people in highest social classes (odds ratio 0.59, 95% confidence interval 0.40 to 0.85). However, the mean age at presentation was 24.8 years for patients whose parents were in the highest social class compared with 33.1 years for those in the lowest social class at birth. Conclusions: Although social class of origin does not seem to be an important risk factor for schizophrenia, it partially determines the age at which patients receive treatment. The relation between low social class at birth and poor outcome may be at least partially mediated through treatment delay.